KEBIASAAN KECIL BERDAMPAK POSITIF TERHADAP KARAKTER (STUDI PUSTAKA DARI NOVEL ATOMIC HABBIT KARYA JAMES CLEAR)) - Hendrisab (El-Rusyd, 2022)
[Small Habits that Have a Positive Impact on Character (Library Study of James Clear's Atomic Habbit Novel)] Purpose This paper presents the importance of forming good habits by doing small things. In the book Atomic Habit, by James Clear published by Gramedia. Reveal how very small changes can grow into extraordinary, life-changing results. Methodology or Approach - used in this paper using a library research method or approach, while data collection is carried out by reviewing and/or exploring several journals, books, and documents (both printed and electronic) as well as sources data and or other information deemed relevant to the study. The finding in this study is that eliminating bad habits and forming good habits is not an instant process. Even so, there are always ways that we can choose to create a better life with positive habits. The conclusion that can be drawn from the Atomic Habbit book is that habit forms include; thinking, recording, repetition 1, storage 1, repetition 2, storage 2, is done repeatedly until it is embedded in the subconscious and accustomed to behavior. While tips from good habits that can be applied in everyday life, are contained in the form of several provisions, including; The first rule, make it visible, the second rule, make it interesting, the third rule, make it easy, and the fourth rule, make it satisfying. How to stop bad habits is; Make it invisible, make it uninteresting, make it difficult, and make it disheartening.